BioSAXS Sample Changer: a robotic sample changer for rapid and reliable high‐throughput X‐ray solution scattering experiments. (1st January 2015) - Round, Adam; Felisaz, Franck; Fodinger, Lukas; Gobbo, Alexandre; Huet, Julien; Villard, Cyril; Blanchet, Clement E.; Pernot, Petra; McSweeney, Sean; Roessle, Manfred; Svergun, Dmitri I.; Cipriani, Florent
<x xml:space="preserve">Abstract</x> Small‐angle X‐ray scattering (SAXS) of macromolecules in solution is in increasing demand by an ever more diverse research community, both academic and industrial. To better serve user needs, and to allow automated and high‐throughput operation, a sample changer (BioSAXS Sample Changer) that is able to perform unattended measurements of up to several hundred samples per day has been developed. The Sample Changer is able to handle and expose sample volumes of down to 5 µl with a measurement/cleaning cycle of under 1 min. The samples are stored in standard 96‐well plates and the data are collected in a vacuum‐mounted capillary with automated positioning of the solution in the X‐ray beam. Fast and efficient capillary cleaning avoids cross‐contamination and ensures reproducibility of the measurements. Independent temperature control for the well storage and for the measurement capillary allows the samples to be kept cool while still collecting data at physiological temperatures. The Sample Changer has been installed at three major third‐generation synchrotrons: on the BM29 beamline at the European Synchrotron Radiation Facility (ESRF), the P12 beamline at the PETRA‐III synchrotron (EMBL@PETRA‐III) and the I22/B21 beamlines at Diamond Light Source, with the latter being the first commercial unit supplied by Bruker ASC.